Childhood mycosis fungoides with a CD8+ CD56+ cytotoxic immunophenotype. (12th February 2015) - Poppe, Heiko; Kerstan, Andreas; Böckers, Martin; Goebeler, Matthias; Geissinger, Eva; Rosenwald, Andreas; Hamm, Henning
<x xml:space="preserve">Abstract</x> Primary cutaneous T‐cell lymphomas mostly occur in patients of middle and higher age. Their rarity and an oftentimes atypical clinical presentation in childhood as well as the reluctance of taking biopsies in children are reasons for a delayed diagnosis. We report the case of an 11‐year‐old boy with a 7‐year history of slowly progressive CD8+CD56+ mycosis fungoides of the cytotoxic immunophenotype. His trunk and extremities were affected by extensive pale‐erythematous patches and plaques with fine scaling. In addition, several poikilodermatous lesions were present on his thighs. Improvement was achieved by topical mometasone furoate treatment. On the basis of our observation, a brief review on cutaneous T‐cell lymphomas in childhood and on CD8+ subtypes in particular is given. Clinicopathological correlation is crucial for establishing the correct diagnosis and for estimation of the prognosis.